Pengembangan Media Video Animasi Berbasis Aplikasi Canva Untuk Menumbuhkan Kesadaran Lingkungan Pada Siswa Kelas III UPTD SD Negeri Kelapa Lima Kupang - Maria Virginia Usmauk; Maxsel Koro; Kurniayu T.R.A. Ratu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The thesis by Maria Virginia Usmauk, student ID 2101140159, Elementary School Teacher Education Program, Year 2025, titled "Pengembangan Media Video Animasi Berbasis Aplikasi Canva Untuk Menumbuhkan Kesadaran Lingkungan Pada Siswa kelas III UPTD SD Negeri Kelapa Lima Kupang," aims to develop animated video media based on the Canva application for social science learning (IPAS) in third grade elementary school. The main problem addressed is the habit of many students frequently littering and showing little care for the cleanliness of the school environment and surroundings, which leads to many diseases and environmental pollution. One effort to overcome this environmental problem is to instill environmental care attitudes in students from an early age, starting with maintaining school cleanliness by disposing of trash in its place. The research method used is Research and Development (R&D). The research subjects consisted of 26 third-grade students. Data was collected through expert validation questionnaires, teacher and student response questionnaires, documentation, and tests. The results of expert validation for media and material experts showed percentages of 87.5% and 91.6%, respectively, with a "very feasible" category. Teachers and students rated the developed media as very practical with percentages of 88.54% and 96.875%, respectively. The n-gain analysis of student learning outcomes showed a percentage of 61%, categorized as "Quite Effective." These findings demonstrate that the animated video media based on the Canva application for social science learning in elementary school is very feasible, practical, and effective in fostering environmental awareness in students.